Mitochondrial DNA Sequence Variants Associated With Blood Pressure Among 2 Cohorts of Older Adults - Thomas W. Buford; Todd M. Manini; John A. Kairalla; Mary M. McDermott; Carlos A. Vaz Fragoso; Haiying Chen; Roger A. Fielding; Abby C. King; Anne B. Newman; Gregory J. Tranah (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Age‐related changes in blood pressure are associated with a variety of poor health outcomes. Genetic factors are proposed contributors to age‐related increases in blood pressure, but few genetic loci have been identified. We examined the role of mitochondrial genomic variation in blood pressure by sequencing the mitochondrial genome. Methods and Results Mitochondrial DNA (mtDNA) data from 1755 participants from the LIFE (Lifestyle Interventions and Independence for Elders) studies and 788 participants from the Health ABC (Health, Aging, and Body Composition) study were evaluated using replication analysis followed by meta‐analysis. Participants were aged ≥69 years, of diverse racial backgrounds, and assessed for systolic blood pressure (SBP), diastolic blood pressure, and mean arterial pressure. After meta‐analysis across the LIFE and Health ABC studies, statistically significant associations of mtDNA variants with higher SBP (m.3197T>C, 16S rRNA; P=0.0005) and mean arterial pressure (m.15924A>G, t‐RNA‐thr; P=0.004) were identified in white participants. Among black participants, statistically significant associations with higher SBP (m.93A>G, HVII; m.16183A>C, HVI; both P=0.0001) and mean arterial pressure (m.16172T>C, HVI; m.16183A>C, HVI; m.16189T>C, HVI; m.12705C>T; all P's<0.0004) were observed. Significant pooled effects on SBP were observed across all transfer RNA regions (P=0.0056) in white participants. The individual and aggregate variant results are statistically significant after multiple comparisons adjustment for the number of mtDNA variants and mitochondrial regions examined. Conclusions These results suggest that mtDNA‐encoded variants are associated with variation in SBP and mean arterial pressure among older adults. These results may help identify mitochondrial activities to explain differences in blood pressure in older adults and generate new hypotheses surrounding mtDNA variation and the regulation of blood pressure. Clinical Trial Registration URL: http://www.ClinicalTrials.gov. Unique identifiers: NCT01072500 and NCT00116194.